Acute scrotum in a neonate caused by renal vein thrombosis. Issue 2 (4th October 2010) - Maas, C; Müller-Hansen, I; Flechsig, H; Poets, C F
Abstract : The authors report on a rare case of neonatal scrotal oedema occurring concurrently with pain upon palpation of the spermatic cord on the first day of life. An ultrasound examination showed poor perfusion of the left testicle and a thrombosis of the left renal vein; intraoperative exploration indicated necrosis of the left testicle without signs of torsion. Gorged vessels with paravasal bleeding were found in the spermatic cord. The authors hypothesise that necrosis of the testicle may result from haemorrhagic infarction caused by renal venous thrombosis. Acute scrotal discolouration with pain upon palpation in neonates is usually attributed to testicular torsion. The authors report a case where these symptoms had a different cause.